The Impact Of Profitability, Firm Size, And Growth Opportunities On The Value Of Property Companies - Eri Kusnanto; Farah Qalbia (Journal of Economic and Leadership, 2024)
This research investigates the impact of profitability, growth opportunities, and firm size on firm value in Indonesian property companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2022. Using regression analysis and t-tests, the study finds that profitability significantly influences firm value, indicating that profitable firms tend to have higher market valuations. In contrast, growth opportunities do not exhibit a significant impact on firm value, suggesting that investors prioritize current profitability over future growth potential in their valuation assessments. Additionally, firm size is found to significantly affect firm value, with larger firms generally commanding higher market valuations due to their perceived stability and market influence. Moreover, the study demonstrates that profitability, growth opportunities, and firm size collectively exert a significant simultaneous influence on firm value. These findings underscore the multifaceted nature of firm valuation in the Indonesian property sector and highlight the importance of considering multiple factors in investment decision-making. .